Innovative Materials and Failure Prevention in Infrastructure: Towards Sustainable Construction with Social Impact - Tarazona, Victor Hugo Verjel; Torres, Dean Andersson Montañez; Reinoso, Dayana Lizeth Chiquin; Doria-Andrade, J. (Journal of Posthumanism, 2025)
This article analyzes the role of innovative materials in the prevention of structural failures and their relationship with sustainability and social impact in construction. Through a multidisciplinary approach, the use of materials such as self-healing concrete, carbon fiber-reinforced polymers, nanomaterials, and recycled materials is examined. The methodology combines recent literature review and relevant case studies. It is shown that the implementation of these materials not only improves the structural strength and durability of infrastructure, but also reduces maintenance costs and generates social benefits by increasing urban resilience and promoting equity in access to safe infrastructure. Finally, a theoretical framework is proposed that articulates technical sustainability with social development, as a guide for decision-making in public policies and engineering projects.